(untitled) (Scientific journal of the Fergana State University, 2023)
The article explores the personality and creativity of the great Uzbek thinker and writer Abdulli Kadiri as a genius of the twentieth century; an attempt is also made to substantiate the natural genetic, socio-cultural, historical and political prerequisites for the formation of the thinker’s personality as a genius. Also, the analysis of the phenomenon of "genius" is the central part of the article.